Amyotrophic lateral sclerosis - Ludolph, Albert C.; Brettschneider, Johannes; Weishaupt, Jochen H. (Current opinion in neurology, 2012)
Purpose of review - The field of amyotrophic lateral sclerosis (ALS) has seen a number of remarkable advances during recent years that will be summarized in this review. - Recent findings - In particular, the progress in the molecular neuropathology with the discovery of pathogenic mutations in TAR DNA binding protein (TARDBP), fused in sarcoma (FUS), ubiquilin2 (UBQLN2) and most recently C9ORF72 (abbreviation for the open reading frame 72 on chromosome 9) has further substantiated the - clinically temporarily forgotten - relation of classic ALS to frontotemporal degeneration (FTD). Also, major progress has been made by the discovery of genes relevant for the disease, and pathogenetic concepts have been suggested which imply that not one, but multiple genetic and cell biological hits are involved in the causation of the disease. Progress in interventional therapies has remained poor; important recent examples are the failure of the interventional lithium and pioglitazone trials. However, a study of a third interventional compound - dexpramipexol - raises substantial hopes that the class of chemicals originally represented by riluzole - benzothiazoles - may provide additional therapeutic progress for ALS patients. - Summary - Tremendous progress has been made in the field of ALS based on recent neuropathological and genetic discoveries. Moreover, the role of metabolism and nutrition in the pathogenesis of the disease is debated and may potentially serve as a future therapeutic target. For the facilitation and cost reduction of clinical trials, the development and international standardization of disease-specific ‘wet’ and ‘dry’ biomarkers is essential.
Gesehen am 17.06.2021